IT Support for Business Process Innovation – Architectural Choices and Design Challenges - Voigt, Matthias; Ortbach, Kevin; Plattfaut, Ralf; Niehaves, Björn (46th Hawaii International Conference on System Sciences, 2013)
For many organizations, business process innovation (BPI) is a crucial factor to ensure competitiveness. BPI can be characterized as a dynamic capability, since it facilitates change in operational processes. Moreover, it involves creative activity, since new and purposeful business processes are created. In this context, choosing and implementing IT tools that are supportive to these two specifics of process innovation can be considered a key success factor for organizations. However, both characteristics lead to challenges concerning the design of a socio-technical system. Companies have to be aware of those challenges in order to make an informed decision on system design. In this paper, we derive and consolidate characteristics of the innovation process. We identify two major properties - 1) task heterogeneity and 2) collaborativeness - and derive key design challenges on both technical and organizational level that these properties pose for the development of either distributed or monolithic process innovation systems.